Professional web design : the best of smashing magazine (Smashing Magazine, 2011)
"this book presents guidelines for professional Web development, including communicating with clients, creating a road map to a successful portfolio, rules for professional networking and tips on designing user interfaces for business Web applications"--Provided by publisher